Smart coating with pH-responsive micro-capsules containing corrosion inhibitors for anti-corrosion of AZ31 magnesium alloys - Nurul Shuhada, Mohamed; Juliawati, Alias; Nasrul Azuan, Alang; A. F., Omar (Faculty Mechanical Engineering, UMP, 2025)
The widespread use of AZ31 magnesium (Mg) alloys in automotive, aerospace, and biomedical applications is often hindered by their high susceptibility to corrosion. In this study, a novel pH-responsive smart coating was developed, integrating multilayer microcapsules containing benzotriazole (BTA) as a corrosion inhibitor and linseed oil (LO) as a self-healing agent to enhance the corrosion resistance of Mg alloys. The BTA in the shell provides immediate corrosion protection by forming a passive barrier layer under acidic or alkaline conditions. At the same time, the LO in the core offers sustained self-healing by sealing defects over time. Dual-functional poly(urea-formaldehyde) (PUF) microcapsules were synthesized via in-situ polymerization, incorporating BTA within a chitosan-alginate multilayer shell and LO in the core. The controlled release behaviour of BTA was analysed in acidic (pH 4) and alkaline (pH 10) conditions, revealing an enhanced release profile in acidic environments, which facilitates targeted corrosion inhibition. The structural and chemical properties of the microcapsules were characterized using FTIR, UV-Vis spectroscopy, SEM-EDX, and optical microscopy. The corrosion protection performance of the smart coating was evaluated on AZ31 Mg alloy substrates using electrochemical impedance spectroscopy. The results confirmed that the smart coating significantly improved the corrosion resistance of the AZ31 Mg alloy, with film resistance (Rfilm) values of 7.211 × 10⁴ Ω·cm² at pH 4 and 7.964 × 10⁴ Ω·cm² at pH 10. These values are higher than those of the epoxy-coated and uncoated AZ31 Mg alloy, indicating the formation of strong passive layers that impede electrolyte penetration. The increased Rfilm shows the effectiveness of coating in enhancing corrosion inhibition and self-healing capabilities under both acidic and alkaline conditions. Overall, this study demonstrates that utilizing biodegradable, pH-responsive multilayer microcapsules is a promising and environmentally friendly approach to protecting magnesium alloys from corrosion. These results suggest that this smart coating could be a practical and environmentally friendly solution for protecting lightweight metals, particularly in vehicles and similar applications.